KUALITAS PERAIRAN SUNGAI RANGAU BERDASARKAN INDIKATOR KOMUNITAS PLANKTON SEBAGAI SUMBER RANCANGAN HANDOUT PADA MATERI PERUBAHAN LINGKUNGAN DI SMA KELAS X - Pratiwi, Dewi Anggi; Yustina, Yustina; Suwondo, Suwondo (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Changes in environment and human activities now is one of the causes of water pollution in various waters such as rivers, lakes, reservoirs and at sea. This study aims to determine the quality of Rangau River waters based on the plankton community indicator. The study was conducted in October 2017 - January 2018 along the Rangau River and was identified in the FKIP Biology laboratory of the University of Riau. The results of the study were integrated to design the handouts. Determination of research station purpose random sampling by setting 8 stations and 3 random sampling. Biological parameters observed were species composition, abundance, fairness index, species richness index, dominance index, and diversity index. Physical-chemical parameters measured are temperature, pH, brightness, current strength, DO, CO, BOD and COD. Data were analyzed descriptively. Based on soil analysis obtained composition type fitoplankton consists of 19 species and composition of type zooplankton consist of 4 species. The result of the analysis of phytoplankton abundance value is quite high compared to zooplankton. Based on the phytoplankton diversity index, the waters quality of Rangau River is classified as mild-moderate. While the index of zooplankton diversity shows the quality waters of the Rangau River classified as medium-heavy. And the result of measurement of physical chemistry factor of water exceeds quality standard with water quality criterion based on BOD, Rangau River classified as mild. Result of research of Rangau River water quality is used as material of material handout design of environmental change precisely water pollution.Keywords: Plankton, river water quality, physic-chemical water factor, handout.